Implementasi Pembelajaran Matematika Berbasis Open Ended Pada Mahasiswa Semester I Jurusan Akuntansi Fakultas Ekonomi Universitas Pamulang - Nelly Budiyarti (Jurnal Riset Teknologi dan Inovasi Pendidikan (Jartika), 2019)
This study aims to describe the implementation of Open Ended-based learning can improve Mathematics learning outcomes of the first semester S1 Accounting students at the University of Pamulang. Data collection is done by observation and tests. The results of the exam in the first cycle, 15 of 35 students or 43% of students passed the material "Relationship of Functions with Derivatives". While in the second cycle, 32 of the 35 students who received grades included in the criteria for graduation, namely between 60-95. There is an increase in learning outcomes and the percentage of students who graduate, from 43% to 91%. It was concluded that Open Ended based learning turned out to be favored by students because it could improve learning outcomes, in addition, students could convey ideas or ideas related to how to solve a Mathematical problem with varied concepts.